Perceptions and Legal Outlooks on Workplace Sexual Harassment in Global Setting: A Review Based Study - Paudel, Manusha; Khanal, Prabha (Historical Journal, 2023)
Globally, sexual harassment is a common phenomenon and occurred before formulating its name sexual harassment. ILO focused on it and said that sexual harassment at work will not be tolerated and must end worldwide. The primary objective of this study is to examine the idea of workplace harassment and its legal aspects globally. This is a review-based study and has been grounded on authentic sites such as google scholar, academia, jstor, and electronic libraries to explore the context. Among a few governments Sweden was the first to adopt legislation and organized seminars and highlighted workplace sexual harassment including anti-bullying laws. Likewise, international organizations and conventions such as CEDAW, ILO, and women's conferences have included provisions on sexual harassment in the workplace. Anti-sexual harassment acts have come into effect in many countries such as Pakistan, Afghanistan, the Philippines, Indonesia, Turkey, and Nepal. Additionally, from the global level, the Me-too movement assisted to speak up on sexual harassment. However sexual harassment in the workplace continues. Despite the sexual harassment acts and laws, employers continue to ignore the incidences of harassment. Therefore, both employers and employees need to work towards creating a safer workspace, and free from harassment by formulating and implementing policies based on the country’s acts and protocols for prevention.